SISTEM INFORMASI GEOGRAFIS PEMETAAAN LOKASI WISATA DI SUMATERA BARAT BERBASIS WEBGIS MENGGUNAKAN QGIS - Fajrillah; Riski Ardiansyah; Triska Andini; Riri Juliani; Mita Trianda Putri; Iswandi Idris (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2022)
The tourist attraction is something that everyone likes, because it offers beauty and happiness for anyone who will visit it, a tourist attraction that can be developed properly will certainly increase income very high. West Sumatra is one of the provinces that has various tourist attractions that can be visited, but due to a lack of information and the absence of instructions that can explain in detail where the position of the tourist attractions are located, therefore tourist attractions in West Sumatra are only partially visited by visitors. Therefore, a study was conducted to address this problem. That is by making a lokasi map to clearly determine the position of tourist objects in West Sumatra, namely the GIS web system for the position of tourist objects in the West Sumatra region by utilizing the QGIS application